2015
DOI: 10.7575/aiac.alls.v.7n.1p.195
|View full text |Cite
|
Sign up to set email alerts
|

Through the Lens of Good Language Learners: What Are Their Strategies?

Abstract: Often times, many English as Second Language (ESL) facilitators speculate why some learners learn faster than other learners. Provided the students were exposed with the same amount of years in the formal education system in Malaysia, the language instructors curious about the variety of performance in the English language among the learners. This study revealed the language learning strategies used by ten successful ESL learners of a private university in Kajang, Selangor, using Oxford's (1990) Strategy Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
6
13
0
Order By: Relevance
“…In addition, affective strategies are placed at the sixth place with the mean score of 3.2963 meaning they are averagely used among the respondents. Nazri et al (2016) in their research among ESL learners in a university revealed exact same findings as in this research which the metacognitive strategies ranked the first followed by compensation, cognitive, social, memory and lastly affective. Similarly, Yunus et al (2013) and Rahman (2020) in their research towards Malaysian gifted students and EFL learners respectively found that metacognitive strategies were used the most meanwhile the least rank was affective strategies.…”
Section: Findings and Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In addition, affective strategies are placed at the sixth place with the mean score of 3.2963 meaning they are averagely used among the respondents. Nazri et al (2016) in their research among ESL learners in a university revealed exact same findings as in this research which the metacognitive strategies ranked the first followed by compensation, cognitive, social, memory and lastly affective. Similarly, Yunus et al (2013) and Rahman (2020) in their research towards Malaysian gifted students and EFL learners respectively found that metacognitive strategies were used the most meanwhile the least rank was affective strategies.…”
Section: Findings and Discussionsupporting
confidence: 85%
“…The least used memory strategy "I used flashcards to remember new English words" (item 6), holding the mean 2.3519. The findings are parallel with Yunus et al (2013), Nazri et al (2016), Ang et al (2017) and Rahman (2020). According to Oxford (2003) memory strategies support learners by enabling them to link concept in second language without necessarily having deep understanding which also often positively associated with second language proficiency.…”
Section: Findings and Discussionsupporting
confidence: 82%
See 3 more Smart Citations